3D-M3: high-spatial-resolution spectroscopy with extreme AO and 3D-printed micro-lenslets - Anagnos, Theodoros; Trappen, Mareike; Tiong, Blaise C. Kuo; Feger, Tobias; Yerolatsitis, Stephanos; Harris, Robert J.; Lozi, Julien; Jovanovic, Nemanja; Birks, Tim A.; Vievard, Sébastien; Guyon, Olivier; Gris-Sánchez, Itandehui; et al. (Applied optics, 2021)
By combining integral field spectroscopy with extreme adaptive optics, we are now able to resolve objects close to the diffraction limit of large telescopes, exploring new science cases. We introduce an integral field unit designed to couple light with a minimal plate scale from the SCExAO facility at NIR wavelengths to a single-mode spectrograph. The integral field unit has a 3D-printed micro-lens array on top of a custom single-mode multi-core fiber, to optimize the coupling of light into the fiber cores. We demonstrate the potential of the instrument via initial results from the first on-sky runs at the 8.2 m Subaru Telescope with a spectrograph using off-the-shelf optics, allowing for rapid development with low cost.